To what extent can the activities of the South Australian Health in All Policies initiative be linked to population health outcomes using a program theory-based evaluation? - Fran Baum; Toni Delany-Crowe; Colin MacDougall; Helen van Eyk; Angela Lawless; Carmel Williams; Michael Marmot (BMC Public Health, 2019)
Abstract Background This paper reports on a five-year study using a theory-based program logic evaluation, and supporting survey and interview data to examine the extent to which the activites of the South Australian Health in All Policies initiative can be linked to population health outcomes. Methods Mixed-methods data were collected between 2012 and 2016 in South Australia (144 semi-structured key informant interviews; two electronic surveys of public servants in 2013 (n = 435) and 2015 (n = 483); analysis of state government policy documents; and construction of a program logic model to shape assessment of the feasibility of attribution to population health outcomes). Results Multiple actions on social determinants of health in a range of state government sectors were reported and most could be linked through a program logic model to making some contribution to future population health outcomes. Context strongly influences implementation; not all initiatives will be successful and experimentation is vital. Successful initiatives included HiAP influencing the urban planning department to be more concerned with the health impacts of planning decisions, and encouraging the environment department to be concerned with the health impacts of its work. Conclusions The theory-based program logic suggests that SA HiAP facilitated improved population health through working with multiple government departments. Public servants came to appreciate how their sectors impact on health. Program logic is a mechanism to evaluate complex public health interventions in a way that takes account of political and economic contexts. SA HiAP was mainly successful in avoiding lifestyle drift in strategy. The initiative encouraged a range of state government departments to tackle conditions of daily living. The broader underpinning factors dictating the distribution of power, money and resources were not addressed by HiAP. This reflects HiAP’s use of a consensus model which was driven by (rather than drove) state priorities and sought ‘win-win’ strategies.